P246 Suspicion-prompted testing reveals missed opportunities for diagnosing new HIV cases among patients with community-acquired pneumonia. (16th November 2010) - Safavi, S; Chua, F J K; Reilly, P; Russell, G K
Abstract : Introduction: National UK policy for HIV testing1 recommends offering an HIV test to all patients with HIV indicator diseases such as tuberculosis (TB), Pneumocystis pneumonia, aspergillosis and bacterial pneumonia. Universal testing is advocated for all adults registering with a GP and all general medical hospital admissions in regions where HIV prevalence is >2/1000 population. Although 'opt out' HIV testing is a standard practice for patients with TB, testing falls far short in other clinical settings. Method: A large number of community-acquired pneumonia (CAP) cases across three south London boroughs where HIV prevalence exceeds 2/10002 are managed at our institution. All cases of CAP in 2008 (with one or more of: radiographic consolidation, CAP clinical case definition fulfilment, positive microbiology or pneumococcal urinary antigenaemia) were included in the present analysis. Demographic, HIV sampling and outcome data were collected. Results: 618 patients (325 or 53% male, 293 female) with a diagnosis of CAP were identified. The majority (500, 81%) were aged >50. Of the total, only 23 (3.7%) patients underwent HIV testing, of whom 1 in 4 (26%) tested positive. Half represented new diagnoses while the remainder had prior documentation of HIV positivity. Overall, 9/60 (15%) of ethnically black (African-Caribbean) patients were tested, compared to only 6/429 (1.4%) of White British patients. The rate of testing varied between age groups: 16% (19/118) of those aged 15–50 were tested, in contrast to only 0.8% (4/500) of patients aged over 50. Information regarding patients were declined testing was not available. Discussion: Of individuals diagnosed with CAP who were HIV-tested, the proportion of 'incident' positive testing (13%) is approximately 5 times higher than expected if a policy of universal testing was practised. HIV testing was more often performed on younger or black patients. Despite serving a high prevalence population, HIV testing at this and likely many other institutions is under-utilised by medical teams even for patients with an HIV indicator pathology. Management of CAP in secondary care represents an opportunity to prevent a delayed diagnosis of HIV. Barriers to HIV testing need to be identified to reduce HIV mortality associated with late diagnosis.